HGAL, a germinal center specific protein, decreases lymphoma cell motility by modulation of the RhoA signaling pathway - Jiang, Xiaoyu (American Society of Hematology, 2010)
HGAL is a germinal center (GC)–specific gene that negatively regulates lymphocyte motility and whose expression predicts improved survival of patients with diffuse large B-cell lymphoma (DLBCL) and classical Hodgkin lymphoma (cHL). We demonstrate that HGAL serves as a regulator of the RhoA signaling pathway. HGAL enhances activation of RhoA and its down-stream effectors by a novel mechanism – direct binding to the catalytic DH-domain of the RhoA-specific guanine nucleotide exchange factors (RhoGEFs) PDZ-RhoGEF and LARG that stimulate the GDP-GTP exchange rate of RhoA. We delineate the structural domain of HGAL that mediates its interaction with the PDZ-RhoGEF protein. These observations reveal a novel molecular mechanism underlying the inhibitory effects of GC-specific HGAL protein on the motility of GC-derived lymphoma cells. This mechanism may underlie the limited dissemination and better outcome of patients with HGAL-expressing DLBCL and cHL.